1994
DOI: 10.2307/3869869
|View full text |Cite
|
Sign up to set email alerts
|

Soybean GH3 Promoter Contains Multiple Auxin-Inducible Elements

Abstract: The soybean GH3 gene is transcriptionally induced in a wide variety of tissues and organs within minutes after auxin application. To determine the sequence elements that confer auxin inducibility to the GH3 promoter, we used gel mobility shift assays, methylation interference, deletion analysis, linker scanning, site-directed mutagenesis, and gain-of-function analysis with a minimal cauliflower mosaic virus 35S promoter. We identified at least three sequence elements within the GH3 promoter that are auxin indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 0 publications
2
96
0
2
Order By: Relevance
“…Two major classes of plant cis regulatory elements characterized to date that contribute to transcriptional regulation upon diverse stimuli are the TGACG-motif and the G-box element, carrying an ACGT core sequence Giuliano et al, 1988;Menkens et al, 1995;SchulzeLefert et al, 1989;Weisshaar et al, 1991). The TGACGmotif and variations thereof are referred to collectively as C-box (nnGACGTCnn) elements (Izawa et al, 1993) and are found in the promoters of a variety of plant genes including the cauliflower mosaic virus (CaMV) 35S promoter (the as-1 element) (Benfey and Chua, 1990;Lam et al, 1989), the enhancers of the nopaline and octopine synthase genes (the nos and ocs elements, respectively) (Bouchez et al, 1989;Feltkamp et al, 1994;Lam et al, 1990), the wheat histone H3 promoter (the hexamer or Hex element) (Mikami et al, 1989), genes regulated by auxin such as GH3 and GmAux28 (Liu et al, 1994;Nagao et al, 1993), and cell wall protein genes (Hong et al, 1987). The G-box (CACGTG) is also a major class of ubiquitous regulatory DNA elements found in plant genomes, a representative of which is the light-regulated RuBP carboxylase small subunit (RBCS) gene (review by Menkens et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Two major classes of plant cis regulatory elements characterized to date that contribute to transcriptional regulation upon diverse stimuli are the TGACG-motif and the G-box element, carrying an ACGT core sequence Giuliano et al, 1988;Menkens et al, 1995;SchulzeLefert et al, 1989;Weisshaar et al, 1991). The TGACGmotif and variations thereof are referred to collectively as C-box (nnGACGTCnn) elements (Izawa et al, 1993) and are found in the promoters of a variety of plant genes including the cauliflower mosaic virus (CaMV) 35S promoter (the as-1 element) (Benfey and Chua, 1990;Lam et al, 1989), the enhancers of the nopaline and octopine synthase genes (the nos and ocs elements, respectively) (Bouchez et al, 1989;Feltkamp et al, 1994;Lam et al, 1990), the wheat histone H3 promoter (the hexamer or Hex element) (Mikami et al, 1989), genes regulated by auxin such as GH3 and GmAux28 (Liu et al, 1994;Nagao et al, 1993), and cell wall protein genes (Hong et al, 1987). The G-box (CACGTG) is also a major class of ubiquitous regulatory DNA elements found in plant genomes, a representative of which is the light-regulated RuBP carboxylase small subunit (RBCS) gene (review by Menkens et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Within two of tbe auxin-responsive elements (termed DI and D4: Table 3) there are two sets of conserved sequence, one of which (TGTCTC) is also present in tbe NDE region of tbe SAUR genes and is similar to the 5' end of motif A oi PS-IAA4/5. Liu et al (1994) also point out that a sequence just 3' to motif A (not shown in Table 3) is similar to part of their DI sequence.…”
Section: Promoter Analysesmentioning
confidence: 99%
“…Nagao et al, Nagao et al, 1993 McClure et al, Nagao et al, 1993Nagao et al, 1993Liu et al, 1994Liu et al, 1994 * Conserved sequence elements shown in bold: note similarity to motif A.…”
Section: Embp-1 and Others (See Ref) Gh3 Gh3mentioning
confidence: 99%
See 2 more Smart Citations